농산물 공동브랜드화 실태와 발전 전망 - 전창곤 (한국농촌경제연구원, 2003)
A Study on the Effective Strategy to make Agricultural Allied Brand With competition among regions and producers growing intense in the agricultural product markets, brand-making becomes even more urgent to cultivate and secure stable markets. To increase economic effect of brand, many organizations are pursuing allied brand. The purpose of this study is to propose the effective strategy to create allied brand. Brand-making for agricultural products are flooded with problems: for instance individual and similar brands, inconsistent quality control, instabe material supply, distorted recognition on brand-making, collusion between individual and allied brand, insufficient legal registration, and poor management. Field survey by subject and type was implemented to analyze success and failure factors of allied brand-making. Even though there are small differences, the success factors can be summarized as thorough quality control, abundant material supply, satisfaction of consumers' needs, and effective marketing. The failure factors include inefficient brand-making, excessive brand utilization, inadequate quality control and commercialization, and poor management. The task of successful brand-making would require maintenance of uniform quality via firm quality management, joint commercialization and scaling, thorough brand management, and effective brand development. The advancing strategies are also important for allied brand-making, and should be closely development of effective brand image, brand naming and design strategy, systemic brand management strategy, and effective brand marketing strategy. Researchers: Jeon Channg-Gon E-mail Address: pds8382@krei.re.kr
Keywords: 농산물; 공동브랜드화; 농산물유통